Sensory profile and physical-chemical analysis of integral grape juice prepared through steam extraction process - Villa, Fabíola; Potrich, Celio; Dall’Oglio, Paulo Antonio (Scientia Agraria Paranaensis, 2018)
For the making of juice of integral, without additive of sugars, as well as well as the elasticized well, the level of milk and flavored. As vegetable materials were used as cultivars Bordô, Tannat, Moscato and Niagara Rosada. The berries were placed without a steam extractor to extract the whole juice. Three types of juices were analyzed: Bordô, Moscato / Niagara Rosada and Tannat. Two extractions were performed for each treatment, considering each extraction as a repetition. As a form of preservation uses a pasteurization. The result is 50%. With the product ready, sensory and physical tests were performed by sampling. Sensory analysis was based on appearance, smell and gustatory parameters, following a Likert scale. Physical, chemical, and concentrated analyzes of grape juice, pH, titratable acidity, ash, soluble solids and alcohol. Three replicates of each analysis were generated, each with a capacity of 500 mL. All samples of whole grape juice within the parameters of current Brazilian legislation. The grape juice was well accepted among the tasters. Integral juice is best elaborated when using a balanced blend between a more intense coloring variety, such as "Bordô" and with more pronounced flavor / aroma, such as Moscato/Niagara Rosada).